Interactive Urban Irrigation Tool for Florida - Kati W. Migliaccio; N. A. Dobbs; William R. Lusher; J. Fan; Michael D. Dukes; Kelly T. Morgan; B. Ferraro (EDIS)
A team from UF/IFAS has developed an app for optimizing your home irrigation system using real-time weather data from the Florida Automated Weather Network (FAWN). Learn more in this 5-page fact sheet written by K.W. Migliaccio, N.A. Dobbs, W.R. Lusher, J. Fan, M.D. Dukes, K.T. Morgan, and B. Ferraro, and published by the UF Department of Agricultural and Biological Engineering, March 2012.